A broader view of the Cathedral: The meaning of the liability rule. Correcting a misapprehension - Calabresi, Guido (2016)
In this article, the author analyses the tort not only from a private view, but also from a public function as part of the legalpolitical- economic structure of a State. Likewise, he analyses the significance of the liability rule and how this social-democratic way of organizing law and entitlements fixes the size of the liability;however, it is an inaccurate description of what occurs in the world, as in the case of eminent domain. Therefore, he claims a more significant economic role for the liability rule.